A tripartite evolutionary game research on information sharing of the subjects of agricultural product supply chain with a farmer cooperative as the core enterprise. (28th May 2021) - Wang, Jiali; Peng, Xue; Du, Yunan; Wang, Fulin
Abstract : In order to explore the interaction law of information sharing behavior of decision‐making subjects in the agricultural product supply chain, this paper establishes a tripartite evolutionary game mathematical model, uses the replicator dynamics equation to analyze the dynamic evolution process of the three‐dimensional dynamic system, and carries out numerical simulation analysis. The results show that there are seven key factors affecting the information sharing decisions of the decision‐making subjects. This paper explores the specific role of these influencing factors and finds ways to improve supply chain performance. Finally, the study proposes four suggestions for supply chain information sharing management.